1984
DOI: 10.1007/bf00173962
|View full text |Cite
|
Sign up to set email alerts
|

Heat flux saturation in hydrodynamic soft X-ray solar flare plasmas

Abstract: The role of heat flux limitation in soft X-ray emitting solar flare plasmas is considered. Simple analytic arguments suggest that flux limitation is likely to be important during the explosive heating phase, even for relatively modest coronal energy fluxes (say < 109 erg cm-2 s -1). This conclusion is reinforced by a detailed flare loop simulation of the heating phase. Since flux saturation effectively 'bottles up' the coronal heat flux, mass motions now assume a dominant role in transferring energy from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…To the extent that α c is an order-unity correction factor (that depends weakly on v e ), this applies also to the heat flux carried in the non-Maxwellian tail of the electron distribution. For a high-density laboratory plasma, though, Mannheimer & Klein (1975) showed that v c scales directly with v e (see also Smith & Lilliequist 1979;Craig & Davys 1984).…”
Section: Heat Conductionmentioning
confidence: 99%
“…To the extent that α c is an order-unity correction factor (that depends weakly on v e ), this applies also to the heat flux carried in the non-Maxwellian tail of the electron distribution. For a high-density laboratory plasma, though, Mannheimer & Klein (1975) showed that v c scales directly with v e (see also Smith & Lilliequist 1979;Craig & Davys 1984).…”
Section: Heat Conductionmentioning
confidence: 99%
“…Zhao et al (2019) conducted forward-modeling analysis based on their 2.5-dimensional magnetohydrodynamics (MHD) simulation, where the formation and eruption of an FR driven by photospheric converging motion in a chromosphere-transition-corona setup is simulated. The setup includes the effects of radiative cooling, anisotropic thermal conduction along the magnetic field lines, gravitational stratification, resistivity, viscosity and the thermal flux saturation effect (Craig & Davys 1984). Zhao et al (2019) concentrated on the large scale evolution and how it appears in various synthetic observational views.…”
Section: Introductionmentioning
confidence: 99%
“…Cowie和McKee [60] 得到饱和的热传导能流公式为F sat =sign(b•∇T)5φρc s 3 b, 其中φ=0.3, ρ是质量密度, c s 是等温声速, sign(x)取x的 正负符号. Craig和Davys [61] 通过耀斑环的数值模拟, 发 现耀斑过程中热传导能流会出现饱和, 物质流动成为 能量输运的主角. 当电子密度很低, 温度标高小于电 子碰撞自由程时, 如在10个太阳半径之外的太阳风里, 需要考虑无碰撞的热传导能流αn e kTv [62] , 其中常数 α≈1, n e 是电子数密度, k是Boltzman常数, v是流体运动 速度.…”
Section: 经典热传导能流是在扩散假设下计算的 当电子unclassified